Facile synthesis of 7-alkyl-1,2,3,4-tetrahydro-1,8-naphthyridines as arginine mimetics using a Horner–Wadsworth–Emmons-based approach - Lippa, Rhys A.; Murphy, John A.; Barrett, Tim N. (Beilstein Journal of Organic Chemistry, 2020)
Integrin inhibitors based on the tripeptide sequence Arg–Gly–Asp (RGD) are potential therapeutics for the treatment of idiopathic pulmonary fibrosis (IPF). Herein, we describe an expeditious three-step synthetic sequence of Horner–Wadsworth–Emmons olefination, diimide reduction, and global deprotection to synthesise cores for these compounds in high yields (63–83% over 3 steps) with no need for chromatography. Key to this transformation is the phosphoramidate protecting group, which is stable to metalation steps.
Keywords: arginine; Horner–Wadsworth–Emmons; integrin; phosphoramidate; tetrahydronaphthyridine

(untitled) - Hatley, R. J. D.; Macdonald, S. J. F.; Slack, R. J.; Le, J.; Ludbrook, S. B.; Lukey, P. T. (Angew. Chem., Int. Ed., 2018)

WO Patent - Anderson, N. A.; Campbell-Crawford, M. H. J.; Hancock, A. P.; Pritchard, J. M.; Redmond, J. M. (Novel compounds, 2016)

(untitled) - Procopiou, P. A.; Barrett, T. N.; Copley, R. C. B.; Tame, C. J. (Tetrahedron: Asymmetry, 2017)

(untitled) - Procopiou, P. A.; Anderson, N. A.; Barrett, J.; Barrett, T. N.; Crawford, M. H. J.; Fallon, B. J.; Hancock, A. P.; Le, J.; Lemma, S.; Marshall, R. P.; Morrell, J.; Pritchard, J. M.; et al. (J. Med. Chem., 2018)

(untitled) - Hutchinson, J. H.; Halczenko, W.; Brashear, K. M.; Breslin, M. J.; Coleman, P. J.; Duong, L. T.; Fernandez-Metzler, C.; Gentile, M. A.; Fisher, J. E.; Hartman, G. D.; Huff, J. R.; Kimmel, D. B.; et al. (J. Med. Chem., 2003)

WO Patent - Cox, J. M.; Ma, L.; Zhou, X.; Haimbach, R. E.; Coleman, P. J.; Zhou, H.; Kelley, D. E.; Stoch, S. A.; Duong, L. T.; Hoek, M. (Composition and methods for treating chronic kidney disease, 2016)

WO Patent - Devasthale, P.; Moore, F.; Zhao, G.; Pieniazek, S. N.; Selvakumar, K.; Dhanusu, S.; Panda, M.; Marcin, L. R. (Cyclobutane- and azetidine-containing mono and spriocyclic compounds as alpha V integrin inhibitors, 2018)

(untitled) - Yasuda, N.; Hsiao, Y.; Jensen, M. S.; Rivera, N. R.; Yang, C.; Wells, K. M.; Yau, J.; Palucki, M.; Tan, L.; Dormer, P. G.; Volante, R. P.; Hughes, D. L.; et al. (J. Org. Chem., 2004)

(untitled) - Anderson, N. A.; Campbell, I. B.; Fallon, B. J.; Lynn, S. M.; Macdonald, S. J. F.; Pritchard, J. M.; Procopiou, P. A.; Sollis, S. L.; Thorp, L. R. (Org. Biomol. Chem., 2016)

(untitled) - Dormer, P. G.; Eng, K. K.; Farr, R. N.; Humphrey, G. R.; McWilliams, J. C.; Reider, P. J.; Sager, J. W.; Volante, R. P. (J. Org. Chem., 2003)

(untitled) - Wang, W.; Feng, X.; Du, H. (Org. Biomol. Chem., 2016)

(untitled) - Ma, W.; Chen, F.; Liu, Y.; He, Y.-M.; Fan, Q.-H. (Org. Lett., 2016)

(untitled) - Chackalamannil, S.; Xia, Y.; Greenlee, W. J.; Clasby, M.; Doller, D.; Tsai, H.; Asberom, T.; Czarniecki, M.; Ahn, H.-S.; Boykow, G.; Foster, C.; Agans-Fantuzzi, J.; et al. (J. Med. Chem., 2005)

(untitled) - Clasby, M. C.; Chackalamannil, S.; Czarniecki, M.; Doller, D.; Eagen, K.; Greenlee, W. J.; Lin, Y.; Tsai, H.; Xia, Y.; Ahn, H.-S.; Agans-Fantuzzi, J.; Boykow, G.; et al. (Bioorg. Med. Chem. Lett., 2006)

(untitled) - Lohrer, B.; Bracher, F. (Tetrahedron Lett., 2018)

(untitled) - Miller, W. H.; Manley, P. J.; Cousins, R. D.; Erhard, K. F.; Heerding, D. A.; Kwon, C.; Ross, S. T.; Samanen, J. M.; Takata, D. T.; Uzinskas, I. N.; Yuan, C. C. K.; Haltiwanger, R. C.; et al. (Bioorg. Med. Chem. Lett., 2003)

(untitled) - Raghavendra, G. M.; Ramesha, A. B.; Revanna, C. N.; Nandeesh, K. N.; Mantelingu, K.; Rangappa, K. S. (Tetrahedron Lett., 2011)

(untitled) - Hudlicky, M. (J. Fluorine Chem., 1989)

(untitled) - Hintermann, L.; Läng, F.; Maire, P.; Togni, A. (Eur. J. Inorg. Chem., 2006)

(untitled) - Bordwell, F. G.; Algrim, D. J. (J. Am. Chem. Soc., 1988)

(untitled) - Aycock, D. F. (Org. Process Res. Dev., 2007)

(untitled) - Subramanyam, V.; Silver, E. H.; Soloway, A. H. (J. Org. Chem., 1976)

(untitled) - Bestmann, H. J. (Angew. Chem., Int. Ed. Engl., 1965)

(untitled) - Motoyoshiya, J.; Ikeda, T.; Tsuboi, S.; Kusaura, T.; Takeuchi, Y.; Hayashi, S.; Yoshioka, S.; Takaguchi, Y.; Aoyama, H. (J. Org. Chem., 2003)

(untitled) - He, W.; Lv, Y.-G.; Hong, T.-Y.; Tong, Y.-B.; Zhu, Z.-P.; Wei, Q.; Guo, C.-Y.; Yu, G.; Yang, J.-K. (ChemistrySelect, 2017)

(untitled) - Motoyoshiya, J.; Isono, Y.; Hayashi, S.; Kanzaki, Y.; Hayashi, S. (Tetrahedron Lett., 1994)

(untitled) - Lehn, J.-M.; Ziessel, R. (Helv. Chim. Acta, 1988)

(untitled) - Barham, J. P.; Coulthard, G.; Kane, R. G.; Delgado, N.; John, M. P.; Murphy, J. A. (Angew. Chem., Int. Ed., 2016)

(untitled) - Ito, Y.; Kobayashi, K.; Saegusa, T. (J. Organomet. Chem., 1986)